Penanda Hubungan Sinonimi dan Antonimi dalam Kohesi Leksikal pada Teks Berita Utama dalam Koran Republika Edisi Februari 2017 dan Relevansinya pada Pembelajaran di Sekolah Menengah Pertama (SMP) - Kusumastuti, Renita, Dra. Atiqa Sabardilla, M.Hum, Drs. Agus Budi Wahyudi, M.Hum, Drs. Andi Haris Prabawa, M.Hum (2017)
Abstract: The objectives of the study describe and explain the analysis of synonym and antonymic linkages and their relevance to Indonesian language learning as learning materials in junior high. This study used descriptive qualitative method. Sources of data from this study comes from the analysis of Republika newspaper February 2017 edition. The results of this study as follows. The results of the analysis of the synonym and antonymic relationship signifiers in February are as follows: free morpheme with bound morphemes there are 22 data, words with words there are 10 data, words with the phrase there are 5 data, sentence with sentence there are 5 data, and phrase with phrase there 3 data. Most synonymy analysis on free and bound morphemes is 22 data. Antonim in the form of opposition relationship there are 3 data, absolute opposition there are 3 data, hierarchial opposition there are 2 data, and pole opposition there are 2 data. The most antonymic analysis is in opposition relations and absolute opposition. The results of this research will be used as learning materials for learning Indonesian language in junior high